Patients’ anesthesia preferences for Cesarean delivery: exploring the role of personality beliefs in spinal vs. General anesthesia - Esra Turunc; Sezgin Bilgin; Sevda Akdeniz; Ozgur Komurcu; Leman Tomak; Yasemin Burcu Ustun; Ersin Koksal; Burhan Dost (BMC Anesthesiology)
Abstract Background This study aimed to compare the personality belief scores of patients who chose either general or spinal anesthesia during cesarean delivery (CD) and explore the relationship between personality beliefs, and anxiety levels. Methods This prospective study included expecting mothers, aged 18–45 years, who were classified as ASA II-III, scheduled for elective CD. Anesthesia (general or spinal) was selected based on the patient’s preference. Patients with emergency CD indications, contraindications to either anesthesia type, or inability to complete the evaluation scales were excluded. After collecting sociodemographic data and medical history, patients completed the Spielberger Trait Anxiety Inventory (STAI II) and Personality Belief Questionnaire Short Form (PBQ-SF). On the day of surgery, patients were asked to complete the Spielberger State Anxiety Inventory (STAI I) in the preoperative waiting room. After discharge, the collected results were analyzed and compared based on the women’s anesthetic choices (general or spinal anesthesia). Results The study included 150 patients, with 71 expressing a preference for spinal anesthesia and 79 indicating a preference for general anesthesia. The dependent, narcissistic, and borderline personality belief scores, as well as the state anxiety (STAI I) scores, were significantly higher in the spinal anesthesia group than in the general anesthesia group (dependent p = 0.003, narcissistic p = 0.013, borderline = 0.018, STAI I = 0.01). These differences had small to medium effect sizes (η² = 0.053, 0.040, 0.034, respectively). Spearman’s correlation analysis revealed weak positive correlations between state anxiety (STAI I) scores and dependent (rho = 0.237, p = 0.004), narcissistic (rho = 0.287, p < 0.001), histrionic (rho = 0.300, p < 0.001), and borderline (rho = 0.231, p = 0.005) personality belief scores.A weak positive correlation was also observed between trait anxiety (STAI II) scores and dependent personality belief scores (rho = 0.193, p = 0.018). Conclusions Women who preferred spinal anesthesia had higher scores in dependent, narcissistic, and borderline personality beliefs compared to those who preferred general anesthesia. Although weak, these personality beliefs were also associated with preoperative anxiety. Although these findings are inconclusive, they indicate that personality traits may influence anesthesia preference for CD. Trial registration The study was registered on ClinicalTrials.gov (Identifier: NCT06795321).